2017
DOI: 10.15605/jafes.032.01.13
|View full text |Cite
|
Sign up to set email alerts
|

Blepharophimosis Ptosis Epicanthus Inversus Syndrome (BPES) Type 1 in an Indian Family

Abstract: Blepharophimosis ptosis epicanthus inversus (BPES) is a relatively rare congenital disorder, which usually presents with classical eye manifestations. In some cases, it is associated with premature ovarian failure (POF). BPES is of two types, type I and type II. Type I is associated with POF along with eyelid malformations, while Type 2 has only eyelid malformations.Here, we report a family of BPES, in whom two sisters presented with secondary amenorrhea. On eye examination, they have blepharophimosis, ptosis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…Blepharophimosis, ptosis, and epicanthus inversus syndrome (BPES) is a developmental disorder and its diagnosis is based on four major features: blepharophimosis, ptosis, epicanthus inversus, and telecanthus. 4,5 All these characteristic features were present in our patient. Patients with BPES have a high incidence of bilateral strabismus and amblyopia.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Blepharophimosis, ptosis, and epicanthus inversus syndrome (BPES) is a developmental disorder and its diagnosis is based on four major features: blepharophimosis, ptosis, epicanthus inversus, and telecanthus. 4,5 All these characteristic features were present in our patient. Patients with BPES have a high incidence of bilateral strabismus and amblyopia.…”
Section: Discussionsupporting
confidence: 66%
“…Most of these case reports had reported 4 and 8 years as the most common age group at the time of diagnosis. [2][3][4][5] BPES has its genetic basis in a mutation of the FOXL2 gene, located on the long arm of chromosome 3 (3q23). Four types of deletions in chromosome 3q have been described in BPES (viz.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies also concluded that the FOXL2 variant results in a relatively mild blepharophimosis-ptosis-epicanthus inversus syndrome (BPES) phenotype (118), which is a rare autosomal dominant genetic developmental disorder in the eyelids and ovary (114). BPES has emerged to have two subtypes: type I is associated with POF, and type 2 has no systemic associations (119), wherein the different amino acid site alterations will lead to the different subtypes (120). The summary of some autosomal gene variants and related functions in the POF.…”
Section: Foxl2mentioning
confidence: 99%
“…Type I BPES is associated with eyelid abnormalities and, notably, female infertility due to premature ovarian failure. Type II BPES only includes eyelid abnormalities with no associated systemic features [ 2 ].…”
Section: Introductionmentioning
confidence: 99%